2020
DOI: 10.3390/ijms21082949
|View full text |Cite|
|
Sign up to set email alerts
|

Crocetin Prevents RPE Cells from Oxidative Stress through Protection of Cellular Metabolic Function and Activation of ERK1/2

Abstract: Age-related macular degeneration (AMD) is a leading cause for visual impairment in aging populations with limited established therapeutic interventions available. Oxidative stress plays an essential role in the pathogenesis of AMD, damaging the retinal pigment epithelium (RPE), which is essential for the function and maintenance of the light-sensing photoreceptors. This study aimed to evaluate the effects of crocetin, one of the main components of Saffron, on an in vitro RPE model of tert-butyl hydroperoxide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…In this model, neuroprotection by saffron was associated with a reduction of intracellular calcium increase induced by ATP and was mediated through saffron action on the purinergic P2X7 receptor [ 83 ]. In parallel, it has been shown in vitro as well that crocetin reduces the effects of oxidative stress induced by tert -butyl-hydroperoxide in the ARPE-19 cell line [ 84 ]. Pretreatment of RPE cells with crocetin prevented apoptosis evidenced by lactate dehydrogenase release, intracellular ATP depletion, and nuclear condensation [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this model, neuroprotection by saffron was associated with a reduction of intracellular calcium increase induced by ATP and was mediated through saffron action on the purinergic P2X7 receptor [ 83 ]. In parallel, it has been shown in vitro as well that crocetin reduces the effects of oxidative stress induced by tert -butyl-hydroperoxide in the ARPE-19 cell line [ 84 ]. Pretreatment of RPE cells with crocetin prevented apoptosis evidenced by lactate dehydrogenase release, intracellular ATP depletion, and nuclear condensation [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…In parallel, it has been shown in vitro as well that crocetin reduces the effects of oxidative stress induced by tert -butyl-hydroperoxide in the ARPE-19 cell line [ 84 ]. Pretreatment of RPE cells with crocetin prevented apoptosis evidenced by lactate dehydrogenase release, intracellular ATP depletion, and nuclear condensation [ 84 ]. Crocetin preserved junctional and cytoskeleton integrity that are essential for RPE functionality [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-VEGF agents are currently used for the treatment of CNV in AMD. Interestingly, a recent study showed that saffron extract ameliorated the retinal degenerative processes in AMD patients, possibly through neuroprotective activities (Di Marco et al, 2019), while another study showed that crocetin prevented retinal pigment epithelia (RPE) from incurring oxidative stress- induced damage and might halt or delay AMD disease progression (Karimi et al, 2020). Additionally, lutein (another carotenoid) has been recommended as a health supplement for AMD patients by the NIH (Melendez-Martinez, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The authors wish to make the following correction to Figure 6B of this article [ 1 ]: the merge image of group “Pre 15min” (row 5, column 3) was also added by mistake as the merge image of group “TBHP only 15min” (row 3, column 3). The images of the DAPI and pERK1/2 single channels are correct for all experimental groups.…”
mentioning
confidence: 99%